Quality of Life in Systemic Lupus Erythematosus - Pantelis Panopalis; Ann E. Clarke (Clinical and Developmental Immunology)
Systemic lupus erythematosus (SLE) is a pervasive disease with wide-ranging effects on physical, psychological and social well-being. As such, a comprehensive assessment of SLE should include several different outcomes, such as quality of life (QoL) and economic costs, in addition to measures of disease activity and damage. In fact, disease effects on QoL are often considered of greater overall importance to patients. Two approaches have been used in the measurement of QoL: generic questionnaires and disease-specific questionnaires. Generic questionnaires are designed to be used across various conditions and populations, whereas disease-specific questionnaires are designed to measure outcomes in one specific disease or condition. The most commonly used measure of QoL is the Medical Outcomes Study Short Form 36 (SF-36), which is a generic measure that is applicable in a variety of conditions, including SLE. Recently, SLE-specific measures have been developed that may prove to be more responsive than generic measures. The hope is that improved outcome measures will allow for better assessment of SLE and eventually facilitate drug development and improve patient care.